A missionariedade do sacerdócio cristão - Feller, Vitor Galdino (Revista Eclesiástica Brasileira, 2025)
O artigo se constitui de cinco pontos: Parte-se da missionariedade da divina Trindade, para apresentar o Pai que, ao gerar eternamente o Filho, é fonte do sacerdócio de Cristo e, nele e por ele, de toda atividade missionária da Igreja, por meio do sacerdócio batismal e do sacerdócio ordenado. Trata-se, em seguida, de três aspectos da missão cristã, focados na prática de três profissões comuns nos relatos evangélicos: pastor, semeador e pescador. Os dois temas (a missionariedade da Trindade e a missão de pastor, de semeador e de pescador) avançam o pensamento para o aclaramento da missionariedade do sacerdócio de Cristo, e, em íntima relação com ele, da missionariedade do sacerdócio batismal dos fiéis e da missionariedade do sacerdócio ministerial dos ordenados. A missão de pastor, semeador e pescador, é evidenciada seja na missionariedade do sacerdócio de Cristo, seja na missionariedade do sacerdócio batismal dos fiéis e na missionariedade do sacerdócio ministerial ou ordenado. Abstract: The article consists of five points. It begins with the missionary nature of the divine Trinity, to present the Father who, by eternally generating the Son, is the source of the priesthood of Christ and, in and through Him, of all the missionary activity of the Church, through the baptismal priesthood and the ordained priesthood. It then deals with three aspects of the Christian mission, focused on the practice of three common professions in the Gospel accounts: shepherd, sower and fisherman. These two themes (the missionary nature of the Trinity and the mission of shepherd, sower and fisherman) advance the thought towards the clarification of the missionary nature of the priesthood of Christ, and, in close relation to it, of the missionary nature of the baptismal priesthood of the faithful and the missionary nature of the ministerial priesthood of the ordained. The mission of shepherd, sower and fisherman is evidenced both in the missionary nature of the priesthood of Christ, in the missionary nature of the baptismal priesthood of the faithful and in the missionary nature of the ministerial or ordained priesthood. Keywords: Missionary nature; Priesthood of Christ; Baptismal priesthood; Ministerial priesthood.